2020
DOI: 10.1002/fuce.202000079
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the Electrochemical Performance of Anode‐supported Solid Oxide Fuel Cells by Meso‐ and Nanoscale Structural Modifications

Abstract: To improve the electrochemical performance of anode-supported solid oxide fuel cells (SOFCs), microextrusion printing and wet infiltration techniques are employed for structural modification on the meso-(10-100 mm) and nanoscale order, respectively. In the mesoscale structural modification, anode ridge structures are fabricated by extruding an anode slurry on the surface of a flat anode disk to extend the electrodeelectrolyte interfacial area. In the nanoscale structural modification, gadolinium-doped ceria (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…This is because the effect of the interface enlargement becomes more significant at lower operating temperatures, which is because the reduction in cell overpotential becomes larger with decreasing operating temperature. This agrees with the conclusion of our previous studies [10, 14].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…This is because the effect of the interface enlargement becomes more significant at lower operating temperatures, which is because the reduction in cell overpotential becomes larger with decreasing operating temperature. This agrees with the conclusion of our previous studies [10, 14].…”
Section: Resultssupporting
confidence: 94%
“…Thus far, various fabrication technologies, such as laserassisted machining and micro powder imprinting [11][12][13], have been proposed for electrode-electrolyte interface enlargement, and enhanced electrochemical performance has been achieved. A more detailed literature review on interfacial modification techniques can be found in our previous reports [10,14]. However, it was reported that the grooved structures fabricated by the subtractive techniques are difficult to control precisely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate the 1D unit cell model we developed, the predicted current-voltage and impedance characteristics were compared with those obtained from an experiment using an anode-supported button cell. The details of the fabrication of this cell are found elsewhere [55] and summarized as follows. First, 60 wt.% NiO powder (FUJIFILM Wako Pure Chemical Corp., Japan) and 40 wt.% YSZ powder (TZ-8Y, Tosoh Corp., Japan) were mixed by planetary ball milling in isopropanol with zirconia balls ( 4.0 mm) at 300 rpm for 3 h. After evaporating the isopropanol, the resultant NiO-YSZ mixture powder was sieved with a 53 µm mesh to remove agglomerates.…”
Section: Cell Fabricationmentioning
confidence: 99%
“…The porous microstructure of SOFC electrodes correlates with the TPBs, gas diffusio and concentration polarization. Adding an interlayer such as an AFL between the electro lyte and anode, and impregnating electrocatalytic particles into the porous anode effec tively increased the TPBs and decreased the contact resistance between the electrolyte and the electrode [93][94][95][96]. However, the AFL and solution impregnation require additiona The porous microstructure of SOFC electrodes correlates with the TPBs, gas diffusion and concentration polarization.…”
Section: Psudo-core-shell Anode By Ultrasonic Spray Pyrolyzed Impregnationmentioning
confidence: 99%